The Colour of Magic. The Light Fantastic - Pratchett T. Terry (The first discworld novels)
Together in one volume, here are the first two Discworld novels, featuring Rincewind the wizard and his Luggage, Twoflower and innocent tourist and Cohen the Barbarian, the world`s oldest and greatest hero. And not to mention Death, who`s not so bad once you get to know him.